The role of non-governmental organizations in trade policy – case study of campaigns against TTIP and CETA in Germany - Wróbel, Anna (Rola organizacji pozarządowych w polityce handlowej – studium przypadku kampanii przeciw TTIP i CETA w Niemczech, 2018)
The aim of this article is to analyze the role of NGOs in organizing public opposition to trade liberalisation on the example of the campaign against TTIP and CETA in Germany. The study was divided into two parts. The first part analyses the increasing importance of NGOs in trade policy, using as an example the actions against the multilateral trading system of the WTO and the chosen preferential trade arrangements. The second part of the study focuses on non-state actors’ activities in Germany opposing the CETA and TTIP negotiations.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 523, s. 400-415
Keywords: Germany; NGOs; free trade; liberalisation; civil society; EU; TTIP; CETA; Niemcy; wolny handel; liberalizacja; społeczeństwo obywatelskie